Adjuvant Treatment for Gastric Cancer: Chemotherapy Versus Radiation. (21st August 2013) - Ashraf, Noman; Hoffe, Sarah; Kim, Richard
Learning Objectives: Summarize trends of adjuvant treatment in gastric cancer. Describe the potential role of adjuvant chemotherapy versus radiation in gastric cancer. Abstract : Gastric cancer is among the leading causes of cancer death worldwide. Surgery is the only curative modality, but mortality remains high because a significant number of patients have recurrence after complete surgical resection. Chemotherapy, radiation, and chemoradiotherapy have all been studied in an attempt to reduce the risk for relapse and improve survival. There is no globally accepted standard of care for resectable gastric cancer, and treatment strategies vary across the world. Postoperative chemoradiation with 5‐fluorouracil/leucovorin is most commonly practiced in the United States; however, recent clinical trials from Asia have shown benefit of adjuvant chemotherapy alone and have questioned the role of radiation. In this review, we examine the current literature on adjuvant treatment of gastric cancer and discuss the roles of radiation and chemotherapy, particularly in light of these new data and their applicability to the Western population. We highlight some of the ongoing and planned clinical trials in resectable gastric cancer and identify future directions as well as areas where further research is needed. Abstract : Gastric cancer is among the leading causes of cancer death worldwide. Surgery is the only curative modality, but mortality remains high because a significant number of patients have recurrence after complete surgical resection. In this review, we examine the current literature on adjuvant treatment of gastric cancer and discuss the roles of radiation and chemotherapy, particularly in light of new data and their applicability to the Western population.